Capital formation and economic development - Rosenstein-Rodan, P. N. (London : George Allen & Unwin Ltd., 1964)
This book seek to formalize the various hypotheses of a systematic nature in models such as have been previously used in India development planning
Includes index.
Includes bibliographical references: p. 162.
oo 27/08/2018
Loans
Keywords: Capital investments; Investments; India